A geometric approach to structural model matching by output feedback in linear impulsive systems - Zattoni, Elena (Zielona Góra: Uniwersytet Zielonogórski)
This paper provides a complete characterization of solvability of the problem of structural model matching by output feedback in linear impulsive systems with nonuniformly spaced state jumps. Namely, given a linear impulsive plant and a linear impulsive model, both subject to sequences of state jumps which are assumed to be simultaneous and measurable, the problem consists in finding a linear impulsive compensator that achieves exact matching between the respective forced responses of the linear impulsive plant and of the linear impulsive model, by means of a dynamic feedback of the plant output, for all the admissible input functions and for all the admissible sequences of jump times.
Keywords: linear impulsive systems; hybrid systems; model matching; disturbance decoupling; geometric approach; structural properties